Paediatric Strategy Forum for medicinal product development in mitogen-activated protein kinase pathway inhibitors: ACCELERATE in collaboration with the European Medicines Agency with participation of the Food and Drug Administration - Pearson, Andrew D. J.; Allen, Carl; Fangusaro, Jason; Hutter, Caroline; Witt, Olaf; Weiner, Susan; Reaman, Gregory; Russo, Mark; Bandopadhayay, Pratiti; Ahsan, Sama; Barone, Amy; Barry, Elly; et al. (European journal of cancer, 2022)
As the mitogen-activated protein kinase (MAPK) signalling pathway is activated in many paediatric cancers, it is an important therapeutic target. Currently, a range of targeted MAPK pathway inhibitors are being developed in adults. However, MAPK signals through many cascades and feedback loops and perturbing the MAPK pathway may have substantial influence on other pathways as well as normal development. In view of these issues, the ninth Paediatric Strategy Forum focused on MAPK inhibitors. Development of MAPK pathway inhibitors to date has been predominantly driven by adult indications such as malignant melanoma. However, these inhibitors may also target unmet needs in paediatric low-grade gliomas, high-grade gliomas, Langerhans cell histiocytosis, juvenile myelomonocytic leukaemia and several other paediatric conditions. Although MAPK inhibitors have demonstrated activity in paediatric cancer, the response rates and duration of responses needs improvement and better documentation. The rapid development and evaluation of combination approaches, based on a deep understanding of biology, is required to optimise responses and to avoid paradoxical tumour growth and other unintended consequences including severe toxicity. Better inhibitors with higher central nervous systempenetration for primary brain tumours and cancers with a propensity for central nervous system metastases need to be studied to determine if they are more effective than agents currently being used, and the optimum duration of therapy with MAPK inhibition needs to be determined.
Dateiversion vom 3. November 2022
Gesehen am 18.01.2023